МОДЕЛЬНЫЙ РАСЧЕТ ПАРАМЕТРА ЭЛЕМЕНТАРНОЙ ЯЧЕЙКИ Si2ZnS ПОЛУЭМПИРИЧЕСКИМ МЕТОДОМ - Хаккулов, М.К. (SCIENCE and SOCIETY, 2023)
By applying quantum mechanical and molecular dynamic techniques, the author has performed calculation of required parameters of bonds (charge state) for base matrix of Si and for silicon with impurity cluster consisting of 3 tetrahedral bonds of Si2Zn2S in the base matrix of Si.
Keywords: molecular mechanics method; semiempirical quantum chemical method; calculation of bond parameters; charge condition; cluster; silicon